Differentially expressed microRNAs targeting genes in key pathways in keratoconus - Nowak-Malczewska, Dorota M.; Swierkowska, Joanna; Gajecka, Marzena (Frontiers in Genetics, 2024)
Introduction: Keratoconus (KTCN) is a corneal ectasia, characterized by a progressive thinning and protrusion of the cornea, with a complex etiology involving genetic, behavioral, lifestyle, and environmental factors. Previous studies indicated that microRNAs (miRNAs) could be involved in KTCN pathogenesis. This in silico study aimed to identify precursor microRNAs (pre-miRNAs) differentially expressed in KTCN corneas and to characterize mature miRNAs and their target genes. Materials and Methods: Expression levels of pre-miRNAs were retrieved from our previously obtained RNA sequencing data of 25 KTCN and 25 non-KTCN human corneas (PMID:28145428, PMID:30994860). Differential expression with FDR ≤0.01 and ≥1.5-fold changes were considered significant. Lists of target genes (target score ≥90) of mature miRNAs were obtained from miRDB. Revealed up-/downregulated miRNAs and their target genes were assessed in databases and literature. Enrichment analyses were completed applying the DAVID database. Results: From a total of 47 pre-miRNAs, six were remarkably upregulated (MIR184, MIR548I1, MIR200A, MIR6728, MIR429, MIR1299) and four downregulated (MIR6081, MIR27B, MIR23B, MIR23A) in KTCN corneas. Out of the 1,409 target genes, 220 genes with decreased and 57 genes with increased expression levels in KTCN samples vs. non-KTCN samples were found. The extracellular matrix (ECM) organization, response to mechanical stimulus, regulation of cell shape, and signal transduction processes/pathways were identified as distinctive in enrichment analyses. Also, processes associated with the regulation of transcription and DNA binding were listed. Conclusions: Indicated miRNAs and their target genes might be involved in KTCN pathogenesis via disruption of crucial molecular processes, including ECM organization and signal transduction.